2013
DOI: 10.1021/ac401715k
|View full text |Cite
|
Sign up to set email alerts
|

High Specific and Ultrasensitive Isothermal Detection of MicroRNA by Padlock Probe-Based Exponential Rolling Circle Amplification

Abstract: In this paper, a padlock probe-based exponential rolling circle amplification (P-ERCA) assay is developed for highly specific and sensitive detection of microRNA (miRNA). The padlock probe is composed of a hybridization sequence to miRNA and a nicking site for nicking endonuclease. Using the miRNA as a template, specific ligation to the padlock probe and linear rolling circle reaction (LRCA) are achieved under isothermal conditions. After multiple nicking reactions, many copies of short DNA products are succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
120
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(125 citation statements)
references
References 51 publications
5
120
0
Order By: Relevance
“…[19][20][21][22][23][24][25][26] The let-7 family of miRNAs in particular has been shown to play significant roles in ovarian, prostate, liver and pancreatic cancer. [27][28][29][30] Since miRNAs are short, polymerase chain reaction (PCR) cannot be carried out on the unmodified target.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23][24][25][26] The let-7 family of miRNAs in particular has been shown to play significant roles in ovarian, prostate, liver and pancreatic cancer. [27][28][29][30] Since miRNAs are short, polymerase chain reaction (PCR) cannot be carried out on the unmodified target.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
“…[21][22][23][24][25][26] This can in principle be extended yet further with hyperbranched RCA. 11 Isothermal detection of miRNAs via rolling circle templates has been reported previously, using templated fluorogenic chemistry 10,31 or DNA-binding fluorescent dyes [22][23][24][25] to report on the products.Experiments in the presence of ARNs showed that the 22mer let-7a RNA could indeed prime DNA synthesis by the highly processive ɸ29 DNA polymerase, using a 50 nt circular DNA complementary to the miRNA as template. Signal appeared above background for reactions as short as 1 h ( Figure S10), and longer polymerase reactions produced yet greater signals.…”
mentioning
confidence: 96%
“…Since many important miRNAs are in quite low abundance in biological samples, many nucleic acid amplification techniques have been employed, such as RT-PCR, 6,7 ligase chain reaction, 8,9 ribozyme amplification, 10,11 loop-mediated isothermal amplification (LAMP), 12,13 exponential amplification reaction (EXPAR), 14 and rolling circle amplification (RCA). 15,16 These methods indeed have greatly improved the sensitivity of miRNAs detection; however, they were highly enzyme dependent and label needed. Therefore, the development of simple, label-free, enzyme-free, and nontarget-amplification methods for miRNA analysis is desired.…”
Section: Introductionmentioning
confidence: 99%
“…[6] However, it is difficult to analyze the miRNAs because of their unique characteristics, including their small size, sequence homology among family members, and low abundance in total RNA samples. [7] So, the strategies for specific and sensitive quantitative detection of miRNAs are in urgent need. [8][9][10][11] Quantitative reverse-transcription polymerase chain reaction (qRT-PCR) is the gold standard for miRNA quantification.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Among these isothermal amplification techniques, rolling circle amplification (RCA) has become increasing popular for the quantitative detection of miRNA. [7,[18][19][20][21][22][23][24][25][26][27] In RCA process, a short DNA (or RNA) is amplified to form a long single-stranded DNA (ssDNA) in the presence of a circular DNA template and special DNA polymerase. The RCA product is a concatemer containing tens to hundreds of tandem repeats that are complementary to the circular template.…”
Section: Introductionmentioning
confidence: 99%